Information system improvement (Case study: Noodle Factory X, Purwokerto, Central Java, Indonesia) - Raden Roro Christina; Vivi Arisandhy; Indah Victoria Sandroto; Khaterine Santika Wijaya (Journal Industrial Servicess, 2021)
A good information system would increase the company’s productivity. One of the most important thing that to be concerned was the procedures. Good and organized procedures would create company standards. Through the research data collection through interview and observation, there were 6 (six) big procedures of Noodle Factory X, Purwokerto, Central Java, Indonesia, which were Material Purchasing Procedure, Material Arrival Procedure, Material Stock Recording Procedure, Finished Good Stock Recording Procedure, Finished Good Shipping Procedure, and Finished Good Selling Procedure. PIECES Analysis were used in this research to analyze the system, including Performance, Information, Economics, Control and Security, Efficiency, and Service. The overall results were material stock counting still used manual system and it could cause human error in doing it, and it was also not real-time count. If the material stock was already real-time count, the material stock recording procedure would not interfere the production process, so it could produce on time. The receipt was still manual, without the company’s identity such as logo and name of the company. Information was not real-time produced. Report service for the management was also a bit slow. Some recommendations were given, such as giving the signature/stamp on the receipt as a proof that it was the receipt that was issued by company, try to implement a simple computerized system, improve the Big Book (for writing the stock), separate the book for material stock and finished good stock at office and at the factory.